CCR5Delta32 deletion as a protective factor in Czech first-wave COVID-19 subjects - Hubáček, Jaroslav; Dušek, Ladislav; Májek, Ondřej; Adámek, Václav; Červinková, Tereza; Dlouhá, Dana; Pavel, Jozef; Adámková, Věra (Physiological research, 2021)
Infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes coronavirus disease (COVID-19), has spread widely around the globe. Significant inter-individual differences have been observed during the course of the infection, which suggests that genetic susceptibility may be a contributing factor. CC chemokine receptor 5 (CCR5), which acts as a co-receptor for the entry of HIV-1 into cells, is promising candidate whose can have an influence on SARS-CoV-2 infection. A genetic mutation known as CCR5Delta32, consisting of a 32-nucleotide deletion, encodes a truncated protein that protects homozygous carriers of the deletion from HIV-1 infection. Similarly, inhibition of CCR5 seems to be protective against COVID-19. In our study, we successfully genotyped 416 first-wave SARS-CoV-2-positive infection survivors (164 asymptomatic and 252 symptomatic) for CCR5?32, comparing them with a population based sample of 2,404 subjects. We found the highest number (P=0.03) of CCR5Delta32 carriers in SARS-CoV-2-positive/COVID-19-asympto-matic subjects (23.8 %) and the lowest number in SARS-CoV-2-positive/COVID-19-symptomatic patients (16.7 %), with frequency in the control population in the middle (21.0 %). We conclude that the CCR5?32 I/D polymorphism may have the potential to predict the severity of SARS-CoV-2 infection.
Keywords: Sequence Deletion; COVID-19; studie případů a kontrol; Humans; Genetic Predisposition to Disease; genetická predispozice k nemoci; sekvenční delece; Gene Frequency; Risk Assessment; Genetic Association Studies; Czech Republic; Receptors, CCR5; Phenotype; ochranné faktory; Risk Factors; Česká republika; Severity of Illness Index; stupeň závažnosti nemoci; Protective Factors; receptory CCR5; rizikové faktory; fenotyp; frekvence genu; hodnocení rizik; lidé; Case-Control Studies; genetické asociační studie